Exploring PIEZO1 DNA methylation in infants with neurodevelopmental disorders - Eleonora Mascheroni; Fabiana Mambretti; Laura Cordolcini; Annalisa Castagna; Elisa Rosa; Niccolò Butti; Andrea Citterio; Nivedita Agarwal; Rosario Montirosso (Frontiers in Psychology)
IntroductionNeurodevelopmental disorders (NDs) are a range of heterogeneous clinical conditions associated with dysfunctional brain development. Variations in DNA methylation (DNAm) have been reported in patients with NDs. Piezo1, which is encoded by the PIEZO1 gene, is a mechanosensitive ion channel protein involved in mechanotransduction across many physiological systems. Its regulation is involved in several diseases of the Central Nervous System (CNS) during adulthood and aging. Although PIEZO1 gene expression is susceptible to epigenetic regulation associated with pathological phenotypes during development, no previous study has explored PIEZO1 DNAm in infants with NDs.MethodsPIEZO1 methylation in 15 CpG sites was assessed in 24 infants with NDs and in 22 infants with typical development (TD) aged between 3 and 36 months.ResultsA principal component analysis (PCA) was run and yielded two factors: principal component1 (PC1) comprising 7 CpG sites and principal component2 (PC2) comprising 8 CpG sites. In PC2, DNAm levels were lower in infants with NDs compared to TD, suggesting hypomethylation in the clinical group, which, in turn, might impact the degree of Piezo1 protein expression.ConclusionWe speculate that PIEZO1 hypomethylation as a potential epigenetic mark could contribute to the poorer mechanical properties of brain tissue in infants with NDs by altering the Piezo1 expression patterns. These findings suggest that the PIEZO1 DNAm status could serve as an early epigenetic marker of NDs, offering promising implications for identifying underlying mechanisms involved in their onset.